Activation effect of soil available nitrogen, manganese and cobalt after addition of different fumigants. (1st April 2022) - Yan, Dongdong; Wang, Qing; Song, Zhaoxin; Fang, Wensheng; Wang, Qiuxia; Li, Yuan; Cao, Aocheng
Abstract: Soil fumigation is a well-established method for controlling soil-borne diseases. Better quantification of soil available nitrogen and trace elements may provide recommendations on the safe and effective application of soil fumigants. The effects of four fumigants on the available soil nitrogen and trace elements (including Mn, Co, Ni, Cu, Zn and Cd) were investigated in the laboratory incubation with agricultural soil. The results showed that soil fumigation increased soil mineral nitrogen and available Mn, Co, Ni. A significant increase of soil NH4 + -N and available Mn was observed in all fumigation treatments. Chloropicrin treatments showed the largest increase of soil NH4 + -N. In addition, chloropicrin and dazomet increased Mn and Co to a greater extent than dimethyl disulfide and 1, 3-dichloropropene in soil. Available Mn content after chloropicrin fumigation has increased by 2.2 times compared with control treatments, and available Co content in dazomet treatments is also 2.8 times more than untreated control. In fumigated soil, the steady increase of soil available elements is beneficial to nutrient uptake by plants. Soil fumigation created an activation effect on soil mineral nitrogen and available trace elements, which may increase their bioavailability to plants and promote plant growth.